Good Measures on Locally Compact Cantor Sets - Karpel, O.M. (Журнал математической физики, анализа, геометрии, 2012)
We study the set M(X) of full non-atomic Borel measures μ on a non-compact locally compact Cantor set X. The set Mμ = {x is in X : for any compact open set U (x is in U) we have μ(U) = ∞} is called defective. μ is non-defective if μ(Mμ) = 0. The set M⁰(X) is subset of M(X) consists of probability and infinite non-defective measures. We classify the measures from M⁰(X) with respect to a homeomorphism. The notions of goodness and the compact open values set S(μ) are defined. A criterion when two good measures are homeomorphic is given.For a group-like set D and a locally compact zero-dimensional metric space A we find a good non-defective measure μ on X such that S(μ) = D and Mμ is homeomorphic to A. We give a criterion when a good measure on X can be extended to a good measure on the compactification of X.